Factors that intervene in exclusive breastfeeding: an integrative review - Abreu, Flávia Corrêa Porto de; Fabbro, Márcia Regina Cangiani; Wernet, Monika (Rev Rene, 2013)
Early weaning is still very present in Brazil, despite the investments in promoting, supporting and protecting breastfeeding. This current integrative review of qualitative researches characterized the factors that intervene in the early weaning and identified the collaborative nuclei for its prevention. Fourteen primary researches composed this study, through a research developed in the following databases: BDENF, LILACS, MEDLINE, and SCIENCE DIRECT, with the descriptors: Breast Feeding, Weaning, and Nursing. Early weaning is related to the socioeconomic context, working mom, previous experiences, and breast problems. These are all considered in the decision-making on weaning. Health professionals need to review their practices to encourage and support breastfeeding, aiming to develop them in an individual and dialogued way together with the women and her family. DOI: https://doi.org/10.15253/2175-6783.20130003000017